Psychometric evaluation of electronic diaries assessing side-effects of hormone therapy. (2nd November 2018) - Tatlock, S.; Abraham, L.; Bushmakin, A.; Moffatt, M.; Williamson, N.; Coon, C.; Arbuckle, R.
Abstract: Objectives: Postmenopausal women (PMW) can experience side-effects (breast pain/tenderness and vaginal spotting/bleeding) associated with estrogen plus progestin therapies (EPTs). To assess these outcomes, the Breast Pain and Tenderness Daily Diary (BPT-DD) and the Vaginal Bleeding and Spotting Daily Diary (VBS-DD) were developed for electronic completion (eDiaries). This study evaluated the psychometric properties of the eDiaries. Methods: The eDiaries were completed daily for 28 days by 202 PMW experiencing breast pain/tenderness and/or vaginal spotting/bleeding while on EPTs. Confirmatory factor analysis (CFA) investigated the BPT-DD structure. Response distributions, test–retest reliability (intraclass correlation coefficient [ICC]), internal consistency (BPT-DD only), and construct validity (via known groups and convergent validity analyses) were assessed. Results: Completion rates were high: over 90% of women missed <3 daily entries. CFA supported the BPT-DD unidimensional structure (Bentler's Comparative Fit Index >0.98). BPT-DD inter-item correlations ( r = 0.77–0.89) and internal consistency (Cronbach's alpha = 0.95–0.97) were high and good test–retest reliability was demonstrated (ICC ≥ 0.70). The eDiaries correlated moderately (>0.40), in a logical pattern with other instruments, supporting convergent validity. Known-groups analyses indicated both measures demonstrated significant differences between patients of differing severity ( p < 0.001). Conclusion: The study provides evidence of strong psychometric properties for the BPT-DD and VBS-DD to assess breast pain/tenderness and spotting/bleeding in PMW.